Porphyrin dye into biopolymeric chitosan films for localized photodynamic therapy of cancer. (20th October 2016) - Ferreira, D.P.; Conceição, D.S.; Calhelha, R.C.; Sousa, T.; Socoteanu, Radu; Ferreira, I.C.F.R.; Vieira Ferreira, L.F.
Highlights: Three different biopolymeric films composed by chitosan, Peg and gelatin were developed. Porphyrin dye was successfully incorporated into the different films. Their spectral-luminescent properties were investigated including fluorescence lifetimes, quantum yields, singlet oxygen formation and Triplet–triplet absorption spectra. Intracellular localization studies of the compounds under study were performed onto HeLa cells. The anticancer activity of all the generated systems was evaluated. Abstract: Porphyrins and some of its derivatives are well known and widely used as photosensitizers (PSs) for Photodynamic Therapy of Cancer (PDT). The present study regards the characterization and evaluation of a synthesized asymmetric porphyrin dye in solution to be used as PS for PDT. This molecule was also incorporated into biopolymeric films composed by chitosan, polyethylene glycol (PEG) and gelatin in order to overtake some of the disadvantages inherent to the PS, but more important, to evaluate the potential of a system composed by the porphyrin/biopolymer to be applied as localized therapeutic agents. FTIR spectroscopy showed a strong interaction between the polymers involved in the preparation of the films under study: film 1: chitosan, film 2: chitosan/PEG and film 3: chitosan/gelatin. Photochemical studies were performed for the dye in solution and into the three different biopolymeric films. Ground state absorption showed the characteristic bands of these kinds of dyes in solution and also incorporated into the films. The films composed by porphyrin/chitosan and porphyrin into chitosan/gelatin, revealed the presence of non-emissive aggregates exhibiting a strong quenching effect in the fluorescence intensity, quantum yields and lifetimes. In this way, the system composed by the porphyrin incorporated into the chitosan/PEG film presents the best fluorescence quantum yield and lifetime. The transient absorption spectra were obtained for all the systems indicating the formation of an excited triplet state of the porphyrins following excitation, which takes special importance in the generation of phototoxic species namely singlet oxygen. Singlet oxygen quantum yields were also determined and the results obtained were very promising for the dye in solution but also for the dye into the different substrates. The release of the dye from the three different films onto a buffer solution was evaluated and we conclude that after a few days the dye was completely released by the substrates in acidic conditions. Confocal microscopy was used for the determination of the intracellular localization of the compound under study onto HeLa cells (human cervical cancer cells line). The evaluation of the PSs anticancer activity assumes special importance for PDT studies. The system should be less toxic in the dark and more active when irradiated, therefore, toxicity in the dark and phototoxicity studies onto HeLa cells were performed.